Students' Attitudes toward Using Literary Works in Learning English in EFL Context - Muhammad Rifqi; Januarius Mujiyanto; Rudi Hartono; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
Literary texts in learning English have been used worldwide in teaching English in various contexts, i.e., first, second, and foreign languages. However, debates among educators about its effectiveness continuously occur. In this research, we tried to examine the students' attitudes toward using literary works for teaching English. Apart from studies about using literary texts in English teaching, this research was done with a combination of imaginative recreation. The research subjects were the 3rd-semester students taking the "Literary Appreciation" English Department at a private university in Semarang in 2020. A hundred and twenty students were involved in this research. Only forty-five students responded to the questionnaires spread to one hundred and twenty. The questionnaires consisted of ten questions concerning the attitude toward using literary texts. The results showed that the overall index of students' attitudes was 3.7, which was classified as a strong attitude toward using literary texts. From the findings, it can be concluded that most students had strong attitudes toward using literary text in English teaching. However, teachers must be attentive to problems that might arise during its implementation.